2016
DOI: 10.1038/ncomms12104
|View full text |Cite|
|
Sign up to set email alerts
|

Bottom-up synthesis of chiral covalent organic frameworks and their bound capillaries for chiral separation

Abstract: Covalent organic frameworks (COFs) are a novel class of porous materials, and offer great potential for various applications. However, the applications of COFs in chiral separation and chiral catalysis are largely underexplored due to the very limited chiral COFs available and their challenging synthesis. Here we show a bottom-up strategy to construct chiral COFs and an in situ growth approach to fabricate chiral COF-bound capillary columns for chiral gas chromatography. We incorporate the chiral centres into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
210
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(217 citation statements)
references
References 36 publications
3
210
2
2
Order By: Relevance
“…[8][9][10] Biomolecules such as enzymes that are created by nature, [11] can well discriminate enantiomers owing to their natural conformations composed of chiral subunits (that is,amino acids) as well as amphiphilic and zwitterionic features capable of providing specific interactions.T his makes them appealing for chiral separation particularly as chiral stationary phases (CSPs) in chromatography if they can be immobilized on some solidstate materials.H erein, we contribute ag eneral approach to immobilize biomolecules into an ew class of solid-state materials,c ovalent organic frameworks (COFs), and the afforded biomolecules&COFs can serve as versatile and highly efficient CSPs towards various racemates in both normal-phase and reverse-phase high-performance liquid chromatography.Emerging as an ew class of crystalline solid-state materials,COFs feature high surface area, low mass density,tunable pore size,high stability,and easily tailored functionality, [12][13][14] which means they hold promise for applications in many fields such as gas storage, [15] photoelectricity, [16] catalysis, [17][18][19] environmental remediation, [20] drug delivery, [21] and functional devices. [22] Thedevelopment of COFs for chiral separation is still in the infancy stage, [23][24][25] primarily relying on the construction of chiral COFs based on chiral monomers.O n the basis of our recent success in immobilizing enzymes into COFs, [26] in this work we present an alternative strategy to introduce chirality into COFs by covalently anchoring aseries of biomolecules,such as amino acids,peptides,and enzymes, onto the channel walls of achiral COFs to form biomolecu-les&COFs (Scheme 1). [27][28][29] We postulate that inheriting the strong chirality and specific interactions from the anchored biomolecules,t he resultant biomolecules&COFs are anticipated to demonstrate high efficiency for chiral separation;in addition, the protective environments provided by COFs [26] and the strong covalent bonding between the biomolecules and COF channel walls thus to prevent the denaturing and leaching of biomolecules make biomolecules&COFs ideal chiral stationary phases in both normal-phase and reversephase HPLC.…”
mentioning
confidence: 99%
“…[8][9][10] Biomolecules such as enzymes that are created by nature, [11] can well discriminate enantiomers owing to their natural conformations composed of chiral subunits (that is,amino acids) as well as amphiphilic and zwitterionic features capable of providing specific interactions.T his makes them appealing for chiral separation particularly as chiral stationary phases (CSPs) in chromatography if they can be immobilized on some solidstate materials.H erein, we contribute ag eneral approach to immobilize biomolecules into an ew class of solid-state materials,c ovalent organic frameworks (COFs), and the afforded biomolecules&COFs can serve as versatile and highly efficient CSPs towards various racemates in both normal-phase and reverse-phase high-performance liquid chromatography.Emerging as an ew class of crystalline solid-state materials,COFs feature high surface area, low mass density,tunable pore size,high stability,and easily tailored functionality, [12][13][14] which means they hold promise for applications in many fields such as gas storage, [15] photoelectricity, [16] catalysis, [17][18][19] environmental remediation, [20] drug delivery, [21] and functional devices. [22] Thedevelopment of COFs for chiral separation is still in the infancy stage, [23][24][25] primarily relying on the construction of chiral COFs based on chiral monomers.O n the basis of our recent success in immobilizing enzymes into COFs, [26] in this work we present an alternative strategy to introduce chirality into COFs by covalently anchoring aseries of biomolecules,such as amino acids,peptides,and enzymes, onto the channel walls of achiral COFs to form biomolecu-les&COFs (Scheme 1). [27][28][29] We postulate that inheriting the strong chirality and specific interactions from the anchored biomolecules,t he resultant biomolecules&COFs are anticipated to demonstrate high efficiency for chiral separation;in addition, the protective environments provided by COFs [26] and the strong covalent bonding between the biomolecules and COF channel walls thus to prevent the denaturing and leaching of biomolecules make biomolecules&COFs ideal chiral stationary phases in both normal-phase and reversephase HPLC.…”
mentioning
confidence: 99%
“…Reaction time was a key factor to keep balance between framework formation and crystallization in the synthesis of highly crystalline COFs 21 . As shown in Figure S2, with the increase of the reaction time, the intensity of the diffraction peaks at 8.31°, 19.20°, 21.23°, and 26.28° improved significantly, which indicated that longer reaction time was beneficial to the formation of better crystalline in MDI‐β‐CD‐modified COF.…”
Section: Resultsmentioning
confidence: 91%
“…However, it is still challenging to design and synthesize homochiral COFs. To date, only several homochiral COFs have been prepared via direct or postsynthetic strategies [110][111][112][113][114][115][116][117]. The application of homochiral COFs in chiral separation is still in its infancy and there is only one research paper exploring the homochiral COFs, CTpPa-1, CTpPa-2, and CTpBD for high resolution GC separation of enantiomers including 1-phenylethanol, 1-phenyl-1propanol, limonene, and methyl lactate [109].…”
Section: Chiral Porous Materials As Chiral Stationary Phases For Hplcmentioning
confidence: 99%